Gangguan Penglihatan Akibat Kelainan Refraksi yang Tidak Dikoreksi - Made Michael Dana (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Background. Refractive error (RE) is an optical defect condition in which the image of the object being viewed does not match the retinal plane, causing blurred vision. Uncorrected refractive error (URE) is the leading cause of visual impairment (VI), also the second leading cause of blindness globally, but it is preventable. Thus, this literature review aims to identify the causes of URE, the health consequences associated with URE, and explore interventions for the prevention of visual impairment due to URE. Method. This research is a literature review study and the library sources used to involve 18 libraries from 1 national journal and 17 international journals. Result. Several studies have shown an increase in URE leads to disability that reduces individual productivity, economic income, and quality of life. The most basic obstacles to correcting URE are economic barriers, access to health care, and socio-cultural constraints. Conclusion. The refractive error reflects a mismatch between the axial length of the eye and its optical power, resulting in blurry images on the retina. Various barriers have been associated with the high prevalence of URE in low-income adults. The use of glasses and a refractive surgery program to correct refractive errors can reduce the URE number.